2014
DOI: 10.1039/c4ce01228c
|View full text |Cite
|
Sign up to set email alerts
|

Metal-enhanced Ge1−xSnx alloy film growth on glass substrates using a biaxial CaF2 buffer layer

Abstract: The Ge1−xSnx(111) alloy formation process at the early stage and later stage of Ge deposition on a biaxial Sn/CaF2 (capping layer + NR)/glass substrate at an elevated growth temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…However, these flakes do not form a continuous film covering the entire mica substrate . In our group we have demonstrated that biaxial continuous Sn films can be grown on the biaxial CaF 2 buffer layer on an amorphous substrate deposited by oblique angle deposition . One can imagine the possibility of depositing SnS films using SnS powders at an oblique angle deposition on an amorphous substrate to induce a biaxial texture instead of through the sulfurization of predeposited Sn.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, these flakes do not form a continuous film covering the entire mica substrate . In our group we have demonstrated that biaxial continuous Sn films can be grown on the biaxial CaF 2 buffer layer on an amorphous substrate deposited by oblique angle deposition . One can imagine the possibility of depositing SnS films using SnS powders at an oblique angle deposition on an amorphous substrate to induce a biaxial texture instead of through the sulfurization of predeposited Sn.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, it is commonly used to evaluate the chemical composition and lattice properties of, for instance, group-IV semiconductors such as strained Si, 4-6 strained Ge, 7-10 SiGe, [11][12][13][14] and GeSn layers. [15][16][17][18][19][20][21][22][23][24][25] The latter are particularly of growing interest because of their relevance to Si-compatible light emission and detection applications in the short-and mid-wavelength infrared, [26][27][28][29][30][31][32][33][34][35] which can lead to the integration of optoelectronic and photonic circuits on complementary metal-oxide-semiconductor (CMOS) platforms. [36][37][38] Previous reports on the vibrational modes of GeSn mainly focused on Ge-Ge longitudinal optical (LO) mode as the analyses relied on the use of 488 nm 15,16 or 532 nm 18-24 excitation lines.…”
mentioning
confidence: 99%
“…The formation of 3D Ge 1−x Sn x VW islands has been observed on various substrates 19,20 including biaxial CaF 2 (111) nanorods. 8 For a more in-depth comparison of the films' morphologies, 8 μm by 8 μm AFM images were used to calculate several roughness parameters. We analyzed the two-dimensional height-height correlation function, HIJr) to extract vertical surface width (or RMS roughness in the surface normal direction), ω, lateral correlation length, ξ, and roughness exponent, α.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Sn has been shown to serve as a surfactant, lowering the temperature needed for Ge crystallization by increasing the diffusion of Ge adatoms, thus the energy costs of producing Ge films can be reduced by alloying with Sn. 8 This is done at no cost to the films' electrical properties because Sn and Ge are in the same chemical group. As a result, Ge 1−x Sn x films have demonstrated potential for application in cost-effective optoelectronics.…”
Section: Introductionmentioning
confidence: 99%